New developments in oral contraception: clinical utility of estradiol valerate/dienogest (Natazia®) for contraception and for treatment of heavy menstrual bleeding: patient considerations - Nelson AL (Dove Medical Press, 2012)
Anita L NelsonObstetrics and Gynecology, David Geffen School of Medicine at UCLA, Harbor UCLA Medical Center, Torrance, California, USAAbstract: Natazia® is a new oral contraceptive with estradiol valerate and dienogest in a unique multiphasic formulation that includes a shortened hormone-free interval. This new formulation has been approved for both contraception and also as a treatment for heavy menstrual bleeding in women who desire to use oral contraceptives as their method of birth control. It is marketed in the US as Natazia® and elsewhere as Qlaira®. This article will review the properties of each of the major new features of this pill: estradiol used in place of ethinyl estradiol, dienogest as the progestin, and the unique dosing pattern of this product. It will also summarize the results of the pivotal clinical trials of contraceptive effectiveness, bleeding patterns, safety and tolerability. The lessons learned from the clinical trials about the effectiveness of this formulation in the treatment of excessive menstrual bleeding will be summarized. Also, results of trials comparing this new pill to other popular formulations for "menstrually-related" symptoms and for potential female sexual dysfunction related to use of oral contraceptives will be presented. This review will suggest how all this information might be used to counsel women about how to use this pill most successfully.Keywords: oral contraceptives, estradiol valerate, dienogest, heavy menstrual bleeding, menorrhagia, dynamic dosing